USING JOURNALS TO INVESTIGATE THE LEARNER’S EMOTIONAL EXPERIENCE OF THE LANGUAGE CLASSROOM - Mercer, Sarah (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract This paper will report on a study conducted as part of a PhD project investigating affective factors in language learning. A study involving 73 advanced tertiary level learners was carried out over the course of one semester (approximately 4 months) in 3 parallel classes. The learners were asked to keep a journal following guidelines on content focusing on their emotional experience of the language classroom. On the basis of an initial analysis of the journals, a questionnaire was constructed to validate the data from the journals. In addition, the questionnaire provided meta-feedback on the use of journals from the learner perspective. This paper will discuss the use of journals as a tool for investigating learner beliefs and emotions and will present the preliminary results of the study.